2019
DOI: 10.1002/jcp.29388
|View full text |Cite
|
Sign up to set email alerts
|

Association of cyclin‐dependent kinase inhibitor 2A/B with increased risk of developing breast cancer

Abstract: There is a growing body of data reporting the association of genetic alterations in chromosome 9P21 with the risk of developing cancer. In the current study, we studied the association of a genetic variant in CDKN2A/B, rs1333049, with the risk of developing breast cancer. A total of 339 participants with and without breast cancer entered to the study. Genotyping was done by the TaqMan real‐time polymerase chain reaction (RT‐PCR) method and gene expression analysis was ran by RT‐PCR. Our data showed that the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…Individuals with a TT genotype had a greater susceptibility for colorectal cancer. In line with our results, recent studies have also indicated the prognostic role of CDKN2A/B in pancreatic, lung, breast, melanoma and ovarian cancers (Qiu et al, 2015[ 19 ]; Seifi et al, 2019[ 24 ]; Campa et al, 2016[ 4 ]; Schuster et al, 2014[ 23 ]). This observation may be explained by the role of CDKN2A/B in suppressing cellular proliferation and inducing tumor cell death.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Individuals with a TT genotype had a greater susceptibility for colorectal cancer. In line with our results, recent studies have also indicated the prognostic role of CDKN2A/B in pancreatic, lung, breast, melanoma and ovarian cancers (Qiu et al, 2015[ 19 ]; Seifi et al, 2019[ 24 ]; Campa et al, 2016[ 4 ]; Schuster et al, 2014[ 23 ]). This observation may be explained by the role of CDKN2A/B in suppressing cellular proliferation and inducing tumor cell death.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, multiple molecular mechanisms have been reported in CRC tumorigenesis including inactivation of tumor suppressor genes (Rahmani et al, 2018[ 20 ]; Soleimani et al, 2018[ 28 ], 2020[ 29 ]; Bahreyni et al, 2018[ 2 ]; Binabaj et al, 2018[ 3 ]). Several genetic association studies have suggested that genetic variations on chromosome 9p21 may be involved in various malignancies including leukemia, glioma, ovarian, breast and pancreatic cancers (Congrains et al,2013[ 5 ]; Dębniak et al, 2005[ 6 ]; Sherborne et al, 2010[ 27 ]; Qiu et al, 2015[ 19 ]; Gu et al, 2013[ 9 ]; Seifi et al, 2019[ 24 ]; Abdeahad et al, 2020[ 1 ]). This region encodes for cyclin‐dependent kinase inhibitors A and B known as CDKN2A/B which contributes in various metabolic and pathological disorders such as diabetes, metabolic syndrome, cardiovascular and Alzheimer diseases (Hannou et al, 2015[ 10 ]; Mehramiz et al, 2018[ 16 ]; Yu et al, 2010[ 34 ]; Zeggini et al, 2007[ 35 ]).…”
Section: Introductionmentioning
confidence: 99%
“… 31 , 32 CDKN2A/p16 has a meaningful association with the risk of BC and it is expected to be a candidate gene for BC. 33 BRCA2 gene is a confirmed BC susceptibility gene, 34 which could lead to the development of BC. 35 HRAS is related to BC and could be a valuable screening biomarker for women.…”
Section: Discussionmentioning
confidence: 99%
“…Correcting the DNA mismatch progress [19] Cell cycle regulation genes TP53 Forming a homotetramer binding to TP53 response elements in DNA [21] PTEN Inhibiting of the DNA proliferation at the G1-S transition [24] DNAH11 Activating of p38 mitogen-activated protein kinase (MAPK) pathway [28] CDKN2A/B Inhibiting of the DNA proliferation at the G1-S transition [30] MICA Modulation in immune response regulation for cell cycles [31] Cell-to-cell adhesion genes CDH1 Coding E-cadherin adhesion protein [32] Metabolism genes PON1 Coding a multifactorial antioxidant enzyme [35] ABC Encoding large membrane proteins relating the energy dependent transport of xenobiotics [38] 3 Breast cancer susceptibility genes [10] . Two cohort studies by Engel and Fischer [11] indicated that the cumulative risk of first-time breast cancer at age 60 was 61.8% for BRCA1 mutation carriers, 43.2% for BRCA2 mutation carriers and 15.7% for non-carriers.…”
Section: Mlh1 /Msh2mentioning
confidence: 99%
“…As a tumor suppressor, cyclin-dependent kinase inhibitor 2A/B (CDKN2A/B) genes inhibit the cell cycle at the G1-S border. By logistic regression, S. Seifi and F. Pouya found that individuals with CC/CG genotypes might have higher risk of breast cancer (OR =2.8, P=0.001) compared with the normal genotypes [30].…”
Section: Othersmentioning
confidence: 99%